German culture in nineteenth-century America: reception, adaptation, transformation - Tatlock, Lynne; Erlin, Matt (Studies in German literature, linguistics, and culture, 2005)
Cultural history : an American refuge for a German idea / Hinrich C. Seeba -- The image of culture, or, What Münsterberg saw in the movies / Eric Ames -- Tacitus Redivivus, or, Taking stock : A.B. Faust's assessment of the German element in America / Claudia Liebrand -- The St. Louis World's Fair of 1904 as a site of cultural transfer : German and German-American participation / Paul Michael Lützeler -- Absolute speculation : the St. Louis Hegelians and the question of American national identity / Matt Erlin -- Reading Alexander von Humboldt : cosmopolitan naturalist with an American spirit / Kirsten Belgum -- Nietzsche : socialist, anarchist, feminist / Robert C. Holub -- Domestic/ated romance and capitalist enterprise : Annis Lee Wister's Americanization of German fiction / Lynne Tatlock -- Pictures of travel : Heine in America / Jeffrey Grossman -- Retroactive dissimilation : Louis Untermeyer, the "American Heine" / Jeffrey L. Sammons -- A tramp abroad and at home : European and American racism in Mark Twain / Linda Rugg -- New country, old secrets : Heinrich Börnstein's Die Geheimnisse von St. Louis (1851) / Gerhild Scholz Williams -- The Americanization of Franz Lieber and the Encyclopedia americana / Gerhard Weiss -- From domestic farce to abolitionist satire : Reinhold Solger's Reframing of the union (1860) / Lorie A. Vanchena